2018
DOI: 10.1016/j.tsc.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of executive functions to creativity in children: What is the role of crystallized and fluid intelligence?

Abstract: Highlights We provide data about the relationships among intelligence, executive functions and creativity.  First study in proposing a SEM model in order to explain the components that predict creative in Spanish-speaking children.  Only cognitive flexibility predicts creativity in children and, in the presence of this executive function, intelligence would not have direct effects on creative potential.  This study has implications for the understanding of the higher-order cognitive mechanisms that explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 78 publications
3
41
1
1
Order By: Relevance
“…Several studies related DT to cognitive flexibility both in adults ( Pan and Yu 2018 ; Benedek et al 2012 ) and children ( Krumm et al 2018 ). Indeed, the flexibility of thought facilitates the production of innovative ideas by switching from one concept (or category) to another and forming remote connections ( Pan and Yu 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies related DT to cognitive flexibility both in adults ( Pan and Yu 2018 ; Benedek et al 2012 ) and children ( Krumm et al 2018 ). Indeed, the flexibility of thought facilitates the production of innovative ideas by switching from one concept (or category) to another and forming remote connections ( Pan and Yu 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In regard to Gf, a study found positive associations between creativity and Gf in children aged from 8 to 14 years, as measured by the Verbal TTCT and both the Kaufman Brief Intelligence Test and Raven’s Standard Progressive Matrices (SPM) ( Krumm et al 2014 ). Another recent work investigated the role of executive function on creativity, demonstrating that—after controlling for the children’s level of intelligence—some specific executive functions, such as shifting and inhibition, make a significant contribution to creativity ( Krumm et al 2018 ). Consequently, the current theories mainly agreed in seeing creative cognition as either a bottom-up or top-down cognitive process ( Beaty et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las investigaciones señalan que a partir de los 4 años el desarrollo cognitivo y creativo de los niños con AC parece depender más del entorno cultural, socioeconómico y educativo que en años anteriores 37 Las investigaciones sugieren que la superdotación se cultiva fomentando la curiosidad intelectual desde la infancia temprana, apoyando la capacidad para conectar el trabajo escolar con un propósito más amplio, fomentando el pensamiento independiente, crítico e investigador a través de entornos desafiantes 38,39 . Sin embargo, en la educación actual el funcionamiento creativo a menudo se atenúa temporalmente cuando los individuos participan en tareas monótonas y repetitivas, dedicadas a la atención externa y la acción inmediata, pudiendo socavar el cultivo a largo plazo de la superdotación.…”
Section: Los Niños Con Ac Son Más Creativosunclassified
“…The concept of giftedness is too broad and prone to controversy when the authors try to define it (Sak, 2020;Smedsrud, 2020). Intelligence, and in particular IQ, is traditionally assumed to be the most decisive variable in the definition of giftedness, however several authors point out its ambiguity and insufficiency for this definition, including other variables related to motivation, personality or creativity in the explanation of high capabilities and high performance (Gagné, 2018;Krumm, Arán, & Gutierrez, 2018;Renzulli, 2012;Sternberg, 2005). This broadening of the variables involved in giftedness highlights the psychological processes inherents to development and learning, introducing the relevance of the executive functions in explaining intelligence and giftedness.…”
Section: Executive Functions and Giftednessmentioning
confidence: 99%